The extent to which physical education and mathematics professors keep pace with teaching the approach curriculum with competencies in the secondary phase A field study of some teachers of the secondary phase of the state of Oum Bouaghi - Ghannem, noureddine; Gagaa , tawfiq; Berrah , hamza (sports creativity, 2025)
The researcher relied on the descriptive method in a survey method, which is an investigation focused on a phenomenon such as educational, educational, or psychological phenomena with the aim of diagnosing them, and the research community was the teachers of physical education in the secondary phase in the state of oum Bouaghi. The researcher used one of the scientific research tools, namely the questionnaire, by designing 03 axes for three hypotheses, in which the questions were varied, including closed, open and half-open, and the researcher concluded a set of conclusions as follows: • The content of the curriculum is unclear and incomprehensible to most secondary education teachers, and this is due to their lack of information about the curriculum. • The content of the curriculum did not bring any changes due to its lack of comprehensiveness and its application in the field. • There are field and cognitive differences between the two curricula, and this indicates that the new curriculum requires the provision and harnessing of capabilities in order to implement it. The researcher recommended the following: • The need to intensify seminars across educational institutions to exchange experiences. Reducing the number of students in the department in order to know the efficiency and ability of each student.